Foreign experience of socially responsible investing: trends, problems and prospects - M. N. Korablin (Вестник университета)
The modern stock market is a constantly changing system that quickly reacts to changes in the environment. The recent events have sharply increased the degree of unpredictability and volatility of global development processes, which has significantly influenced the formation activity of such a segment of this market as socially responsible investing (hereinafter referred to as SRI). The article considers the dynamics of the foreign SRI market, analyses the main forms of state support for SDI in foreign countries as the most significant components for the effective functioning of the SRI ecosystem, highlights the major problems of the SRI market at the current stage. It is shown that at present one of the key challenges in the development of the SRI market is lack of a generally accepted integrated methodology, standards and methods for valuation and accounting of the allocation of securities and use of income from them precisely in connection with the ESG (еnvironmental, social, and governance) agenda. It leads to difficulties in assessing the SRI effectiveness, misuse of investments (greenwashing), to decreased trust in the instruments of the SRI market. The development of a unified approach to the system of assessing the effectiveness of SRI, the formation of common criteria and principles of work in the field of responsible investment will contribute to improving the social life of society, solving environmental problems, and more productive economic development of countries.